Comparison of commercially available antibodies for the detection of phosphorylated alpha‐synuclein in primary culture of ENS. Issue 6 (13th March 2022) - Lassozé, Simon; de Guilhem de Lataillade, Adrien; Oullier, Thibauld; Neunslist, Michel; Leclair‐Visonneau, Laurène; Derkinderen, Pascal; Paillusson, Sébastien
Abstract: Background: It is now well established that phosphorylated alpha‐synuclein histopathology, the pathologic hallmark of Parkinson's disease (PD) is not limited to the brain but also extends to the enteric nervous system (ENS). This observation led to the hypothesis that the ENS could play a pivotal role in the development of PD. Research on the enteric synucleinopathy has, however, been hampered by difficulties in detecting phosphorylated alpha‐synuclein in the ENS by Western blotting, even when the transferred membrane is fixed with an optimized protocol. This suggests that the available antibodies used in previous studies lacked of sensitivity for the detection of phosphorylated alpha‐synuclein at Ser129 in enteric neurons. Here, we evaluated three recent commercially available phospho‐alpha‐synuclein antibodies and compared them to two antibodies used in previous research. Methods: The specificity and sensitivity of the 5 antibodies were evaluated by Western blot performed with recombinant alpha‐synuclein and with protein lysates from rat primary cultures of ENS. In primary culture of ENS, additional experiments were performed with the most specific antibody in order to modulate alpha‐synuclein phosphorylation and to validate its utilization in immunofluorescence experiments. Results: The rabbit monoclonal antibody D1R1R uniquely and robustly detected endogenous phosphorylated alpha‐synuclein at Ser129 in rat primary culture of ENS without any non‐specific bands, allowing for a reliable analysis of phosphorylated alpha‐synuclein regulation by pharmacologic means. Conclusions and inferences: Using D1R1R antibody together with the optimized protocol for membrane fixation may help deciphering the signaling pathways involved in enteric alpha‐synuclein post‐translational regulation in PD. Abstract : The rabbit monoclonal D1R1R antibody specifically detects endogenous alpha‐synuclein phosphorylated at Ser129 in rat primary culture of ENS in Western blot. This antibody also works for immunofluorescence experiments. The D1R1R antibody may help deciphering the signaling pathways involved in the regulation of enteric alpha‐synuclein phosphorylation in Parkinson's disease. Scale bar is 100 µm.